Mitochondrial metabolic rescue in post-COVID-19 syndrome: MR spectroscopy insights and precision nutritional therapeutics - Chen, Li-zhen; Cai, Qi; Zheng, Peng-fei (Frontiers in Immunology, 2025)
Post-COVID-19 Condition (PCC), impacting 30–90% of survivors, is characterized by persistent fatigue and metabolic dysfunction, often linked to underlying mitochondrial impairment. This review examines current evidence on mitochondrial-targeted nutrition therapies, with a focus on magnetic resonance spectroscopy (MRS) as a tool for assessing metabolic recovery. Key findings highlight reduced adenosine triphosphate (ATP) production, heightened oxidative stress, and disrupted mitochondrial biogenesis- metabolic abnormalities that closely mirror those seen in chronic fatigue syndromes. While mitochondrial dysfunction is recognized as central, debate continues on whether systemic inflammation or direct viral damage primarily drives these abnormalities. Current evidence supports nutrients, such as, CoQ10, NAC, and creatine for restoring energy metabolism and reducing oxidative stress. MRS biomarkers (τPCr, Qmax), offer valuable tools for monitoring personalized intervention. However, several limitations persist, including variability in nutritional protocols, inconsistencies in MRS methodologies, and limited consideration of microbiome-psychosocial interactions. Most clinical trials focus on short-term outcomes, lacking data on long-term efficacy or stratification based on mitochondrial dysfunction severity. Future research priorities include multi-omics investigations into mitochondrial-epigenetic interactions, the development of targeted antioxidants, and exploration of engineered microbial metabolites. Standardizing MRS protocols, validating composite endpoints, and optimizing nutrient delivery systems require interdisciplinary collaboration. This review advocates for a precision medicine approach, combining MRS-based metabolic profiling with personalized nutritional strategies, to address the multifactorial nature of PCC and advance clinical translation.